Intensidad de luz solar en el establecimiento de Aniba rosaeodora Ducke en Yurimaguas, Loreto - Ocmin Trigoso, Betty Graciela (2017)
The present research work was carried out in the Loreto region, with the objective of knowing the development of the Aniba Rosaeodora Ducke species in a natural environment with respect to the intensity of sunlight in its establishment with different associations of forest species. The research is of the experimental, quantitative and inferential type, at a basic level, where the population were all the plants of five associations established in the Center for Research, Teaching and Agroforestry Production (CEPIAGRY). According to the results obtained, the main conclusions are: the different intensities of sunlight on the ground measured with the SCHWYZ sc105 luxmeter, composed of a digital chronometer and a graduated photodetector on a scale of 2,000, 20,000 and 50,000 lux, influence the establishment of Aniba Rosaeodora Ducke plants. That for its establishment is in the range of 31.8% to 40.4% of sunlight intensity, and survival was evaluated by counting at 30, 60, 90 and 180 days. Regarding the association with other species, it was determined that the Simarouba Amara species was vital for the optimal establishment of this species.